Weird ties? Growth, cycles and firm dynamics in an agent-based model with financial-market imperfections - Mauro Napoletano; Domenico Delli Gatti; Giorgio Fagiolo; Mauro Gallegati (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2005)
This paper studies how the interplay between technological shocks and financial variables shapes the properties of macroeconomic dynamics. Most of the existing literature has based the analysis of aggregate macroeconomic regularities on the representative agent hypothesis (RAH). However, recent empirical research on longitudinal micro data sets has revealed a picture of business cycles and growth dynamics that is very far from the homogeneous one postulated in models based on the RAH. In this work, we make a preliminary step in bridging this empirical evidence with theoretical explanations. We propose an agent-based model with heterogeneous firms, which interact in an economy characterized by financial-market imperfections and costly adoption of new technologies. Monte-Carlo simulations show that the model is able jointly to replicate a wide range of stylised facts characterizing both macroeconomic time-series (e.g. output and investment) and firms' microeconomic dynamics (e.g. size, growth, and productivity).
Keywords: E32; G30; L11; O40; 330; Financial Market Imperfections; Business Fluctuations; Economic Growth; Firm Size; Firm Growth; Productivity Growth; Agent-Based Models; Finanzmarkt; Unvollkommener Markt; Konjunktur; Wirtschaftswachstum; Technischer Fortschritt; Unternehmenswachstum; Theorie